MODES OF SARS-COV-2 TRANSMISSION - Patel, Nilesh D.; Desai, Kairavi J.; Patel, Shirishkumar M. (Faculty of Vocational Studies, Universitas Airlangga, 2021)
Background: On 12th December 2019, pneumonia of unknown etiology was reported in number of human cases from Wuhan, central China. On 11th February 2020, the WHO named the disease COVID-19, short for